The Effectiveness of Providing Rewards and Punishment for Moral Development of Early Childhood - Dina Amalia; Anita Afrianingsih; Sehla Safira Damayanti (Universitas Nahdlatul Ulama Surabaya, 2023)
The events that are currently occurring are indeed a lot of problems related to the provision of rewards and punishment, especially in the parenting patterns given by parents to their children. So it can increase or even reduce children's moral development. Therefore, there are many cases of beatings and various punishments received by children, such as locking children in their rooms, hitting their body parts, and using harsh words. This research is a form of social research which aims to analyze and summarize various conditions, as a social reality phenomenon in the form of rewards and punishments in the moral development of early childhood. It involved 39 children from KB Permata Kita Hadiwarno Mejobo Kudus. Data collection takes the form of observation, interviews, and documentation. The results of this research are that through rewards children are more confident and brave in making decisions, while punishment can be done through behavioral actions, education and strengthening motivation to avoid unwanted behavior. The conclusion of this research is that through reward and punishment, children know what behavior is right and wrong, so that it has an impact on the child's character effectively and efficiently to be applied in everyday life.